2016
DOI: 10.1007/s13205-016-0393-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacterial endophytes of Curcuma longa L.

Abstract: Fourteen endophytic bacterial isolates were isolated from the rhizome of Curcuma longa L. were characterized on the basis of morphology, biochemical characteristics and 16S rRNA gene sequence analysis. The isolates were identified to six strains namely Bacillus cereus (ECL1), Bacillus thuringiensis (ECL2), Bacillus sp. (ECL3), Bacillus pumilis (ECL4), Pseudomonas putida (ECL5), and Clavibacter michiganensis (ECL6). All the strains produced IAA and solubilized phosphate and only two strains produced siderophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 36 publications
5
71
0
8
Order By: Relevance
“…However, isolate MD12BGroot isolated from the root of Bruigeria gymnorhiza obtained from Mida creek and Gazi bay and isolate MA4XGleaf isolated from leaves of Xylocarpus granatum obtained from Mida creek did not show presence of amylases indicating the enzyme is not actively expressed. Similar studies on bacterial endophytes of Curcuma have shown the presence of amylases in the Bacillus species [26].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, isolate MD12BGroot isolated from the root of Bruigeria gymnorhiza obtained from Mida creek and Gazi bay and isolate MA4XGleaf isolated from leaves of Xylocarpus granatum obtained from Mida creek did not show presence of amylases indicating the enzyme is not actively expressed. Similar studies on bacterial endophytes of Curcuma have shown the presence of amylases in the Bacillus species [26].…”
Section: Discussionsupporting
confidence: 66%
“…Endophytes are microbes that inhabit asymptomatically in the living tissues of plants without causing any substantive negative effect [1]. They colonize the plant tissue both inter-and intracellularly where they exhibit complex interactions with their host [2].…”
Section: Introductionmentioning
confidence: 99%
“…[35] In early 2018, the same company started to supply ashoe manufacturer based in San Francisco with ethylene vinyl acetate (EVA) produced from sugarcane-based ethanol. [36] As renewable chemicals companies grow in size and financial strength thanks to revenues from fine chemical and specialty polymer sales,t hey will be increasingly able to target commodity-type polymers starting from immensely abundant lignocellulosic biomass (731 million tonnes of rice straw alone), [37] rather than from vegetable oils or crops.…”
Section: New Technologyn Ew Raw Materialsmentioning
confidence: 99%
“…These strains previously reported as endophytes in different plant species like Bacillus aerius from Spharanthus indicus [22], Pantoea agglomerans from citrus [23], Serratia nematodiphila from Solanum nigrum [24], Enterobacter sp. from Curcuma longa L [25]. Many endophytic microorganisms have the potential to produce IAA.…”
Section: Discussionmentioning
confidence: 99%